2019
DOI: 10.1177/1120700019835160
|View full text |Cite
|
Sign up to set email alerts
|

Causes of in-hospital mortality after hip fractures in the elderly

Abstract: Objectives: Although there are numerous studies reporting early mortality after hip fracture, the incidence and aetiology of in-hospital mortality following hip fractures is largely unknown. This study aimed to determine the causes and the incidence of in-hospital mortality in patients with a hip fracture who received surgical treatment. Methods: This was a multi-institutional retrospective study identifying 2464 consecutive patients >65 years of age who were treated for a hip fracture from 2000 to 2016 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 44 publications
3
45
2
9
Order By: Relevance
“…Kayani et al reported a similar mortality rate for COVID-negative hip fractures [7]. This rate has been previously reported to be as high as 3-5% during non-COVID times [8,9]. This raises the controversial issue of whether SARS-CoV-2 detection is sensitive enough or not in hip fracture patients [10].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Kayani et al reported a similar mortality rate for COVID-negative hip fractures [7]. This rate has been previously reported to be as high as 3-5% during non-COVID times [8,9]. This raises the controversial issue of whether SARS-CoV-2 detection is sensitive enough or not in hip fracture patients [10].…”
Section: Introductionmentioning
confidence: 84%
“…Patients were not transferred to their corresponding bed/floor until the test was ready. Median time to rRT-PCR results was six hours (interquartile range [IQR], [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. No surgeries were performed with a pending rRT-PCR result.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the fracture group had more deaths from septic shock and multiple organ dysfunction than the CG, which supports our hypothesis. Studies by Groff [30], Dodd [31] and many scholars have also confirmed the association between secondary infection after fracture and patient death.…”
Section: Discussionmentioning
confidence: 84%
“…Although the chance of death is increased in patients with OS with systemic comorbidities, attention should be paid to the fact that these patients with additional AMD diagnosis have a higher risk of spine and hip fractures and subsequent death caused by fractures. 18 19 Therefore, we should aggressively treat AMD to prevent fractures in patients with OS if they are not affected by severe systemic diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Taiwan’s population is ageing at an alarming rate 15 ; OS and related fractures pose an unprecedented threat to the elderly population in Taiwan since the prevalence of OS increases rapidly with age. 14 As fractures in the elderly would contribute to a higher probability of mortality despite promptly surgical intervention, 18 19 potential risk factors for individuals vulnerable to fractures, such as those with OS, should be further investigated and identified.…”
Section: Introductionmentioning
confidence: 99%